Diagnostic value of 18F-fluorodeoxyglucose uptake parameters to differentiate rheumatoid arthritis from other types of arthritis. Issue 25 (June 2017) - Bhattarai, Anu; Nakajima, Takahito; Sapkota, Santosh; Arisaka, Yukiko; Tokue, Azusa; Yonemoto, Yukio; Tsushima, Yoshito
Abstract : Abstract: We aimed evaluate 18 F-fluorodeoxyglucose uptake at major joints for differentiating patients with rheumatoid arthritis (RA) from those with non-RA arthritis using 18 F-fluorodeoxyglucose (FDG)-positron emission tomography (PET). Eighteen patients with RA (13 women; age, 66.8 ± 13.2 years) and 17 patients with non-RA (6 women; age, 50.8 ± 12.5 years) were included. Twelve joints of each patient were examined: shoulder, elbow, wrist, hip, knee, and ankle on both sides. A visual scoring (VS) system was used; quantitative parameters such as maximum standardized uptake value (SUVmax), metabolic active volume (MAV), and total lesion glycolysis (TLG) were evaluated. Total score and value of each parameter were compared between the RA and non-RA groups. Total VS score (mean, 37.7 ± 9.0 vs 21.9 ± 7.2; P < .0001) and SUVmax (mean, 28.1 ± 8.5 vs 17.9 ± 5.8; P < .001) were significantly higher in the RA group than in the non-RA group. A significant between-group difference was also observed with respect to total MAV (608.3 ± 370.7 vs 176.5 ± 217.8; P < .001) and total TLG (1139.3 ± 759.1 vs 289.5 ± 395.4; P < .001). Receiver operating characteristic curve analysis revealed that total VS had the highest area under curve (.92), with sensitivity and specificity of 88.9% and 76.4%, respectively. Quantitative PET parameters could differentiate RA from non-RA. Total VS score, however, appears to be the best convenient qualitative tool for diagnosing RA.